In vitro and in vivo investigation of cardiotoxicity associated with anticancer proteasome inhibitors and their combination with anthracycline. (27th August 2019) - Pokorna, Zuzana; Jirkovsky, Eduard; Hlavackova, Marketa; Jansova, Hana; Jirkovska, Anna; Lencova-Popelova, Olga; Brazdova, Petra; Kubes, Jan; Sotakova-Kasparova, Dita; Mazurova, Yvona; Adamcova, Michaela; Vostatkova, Lucie; et al.
Abstract: Although proteasome inhibitors (PIs) are modern targeted anticancer drugs, they have been associated with a certain risk of cardiotoxicity and heart failure (HF). Recently, PIs have been combined with anthracyclines (ANTs) to further boost their anticancer efficacy. However, this raised concerns regarding cardiac safety, which were further supported by several in vitro studies on immature cardiomyocytes. In the present study, we investigated the toxicity of clinically used PIs alone (bortezomib (BTZ), carfilzomib (CFZ)) as well as their combinations with an ANT (daunorubicin (DAU)) in both neonatal and adult ventricular cardiomyocytes (NVCMs and AVCMs) and in a chronic rabbit model of DAU-induced HF. Using NVCMs, we found significant cytotoxicity of both PIs around their maximum plasma concentration (cmax ) as well as significant augmentation of DAU cytotoxicity. In AVCMs, BTZ did not induce significant cytotoxicity in therapeutic concentrations, whereas the toxicity of CFZ was significant and more profound. Importantly, neither PI significantly augmented the cardiotoxicity of DAU despite even more profound proteasome-inhibitory activity in AVCMs compared with NVCMs. Furthermore, in young adult rabbits, no significant augmentation of chronic ANT cardiotoxicity was noted with respect to any functional, morphological, biochemical or molecular parameter under study, despite significant inhibition of myocardial proteasome activity. Our experimental data show that combination of PIs with ANTs is not accompanied by an exaggerated risk of cardiotoxicity and HF in young adult animal cardiomyocytes and hearts.